THE CORRELATION OF PARENTING PATTERN WITH EMOSIONAL QUESTION AT PRE-SCHOOL AGE CHILDREN (3-5 YEARS) IN EARLY CHILDHOOD EDUCATION MUSLIMAT GETAS CEPU BLORA - Amelia Nur Hidayanti (The Shine Cahaya Dunia Kebidanan, 2022)
Background; The parenting pattern means how parents treat children, educate, guide and discipline and protecting their children in achieving process maturity, up to attempt the formation of the expected norms of society at large. Parenting pattern will also affect the emotional question in Early Childhood Education Muslimat Getas Cepu Blora. This study aims to determine the relationship between parenting parents with emotional question (EQ) in pre-school age children (3-5 years) in Early Childhood Education Muslimat Getas Cepu Blora. Method; This research method descriptive correlative study with Cross Sectional approach, with a sampling of saturated sample 32 parents and 32 childrens in early childhood education Muslimat Getas Cepu Blora. This research used questionnaires and checklists. Result; The results showed that the correlation analysis results obtained Kendal Tau correlation coefficient 0.445 with p value = 0.006 <P = 0.05, so it can be decided that the research hypothesis which states: "There is a relationship between parenting pattern with emotional question (EQ) of pre-school children (3 - 5 years) Muslimat Getas Cepu Blora in Early Childhood Education", is accepted. The results of analysis to obtain correlation coefficient 0.445 indicates that the degree of relationship parenting parents with children's emotional intelligence is a relationship that is because it is on the correlation index from 0.4 to 0.6. Conclusion; Parents should use democratic parenting in raising their children because with democratic parenting children get an explanation of why something is allowed or not to be done and children are appreciated and given opportunities, so it is hoped that children's emotional intelligence can develop in a better direction.